Desfechos perinatais decorrentes do manejo de gestações com crescimento intrauterino restrito com diferentes protocolos. - de Melo Silva, Laís Nascimento; Alves da Silva, Érika Maria; da Silva Vieira Araújo, Manoella Mirella; Tavares Souza, Gracielly Karine; de Souza, Auricarla Gonçalves; Britto de Oliveira Vieira, Bárbara Regina; de Souza Lima, Marcelo Marques; do Nascimento Paixão, Gilvânia Patrícia (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2025)
Objective: to describe perinatal outcomes using different protocols for managing pregnancies with intrauterine growth restriction in a maternal and child referral hospital. Method: a cross-sectional, descriptive study with a quantitative approach, conducted using medical records of patients with intrauterine growth restriction admitted to a referral service in 2017 and 2019. Management with different protocols established in 2017 and 2019 was considered, with the latter suggesting waiting for delivery until 37 weeks of gestation, depending on ultrasound scan and Doppler assessment. Clinical-obstetric and neonatal variables were evaluated. The data were analyzed using the Statistical Package for Social Sciences program, with descriptive statistics, absolute and relative frequencies, and measures of central tendency and dispersion. Results: 36 binomials from 2017 and 78 from 2019 were included. Regarding outcomes, in 2017 there was a higher prevalence of Apgar scores below 7 at one minute, lower gestational age at pregnancy termination, and greater need for neonatal ventilatory support. Conclusion: although slight differences were observed between the years, the most unfavorable neonatal outcomes were identified in 2017. Thus, it can be assumed that there is a positive advantage in the protocol established in 2019.